Medium‐term assessment of cardiac function in pediatric cancer survivors. Comparison of different echocardiographic methods, cardiac MRI and cardiac biomarker testing in adolescent cancer survivors. Issue 2 (20th December 2016) - Shah, Sanket S.; McClellan, Wendy; Knowlton, Joshua Q.; Mehta, Jeet; Goudar, Suma; Ferguson, Angela; Sherman, Ashley; Shirali, Girish; Fulbright, Joy
Abstract : Purpose: To evaluate the feasibility and correlation of 3D echocardiography (echo) and cardiac biomarkers with cardiac MRI, in surveillance of cardiac function for cancer survivors. Methods: Subjects ≥10 years of age who have survived >2 years after completion of cancer treatment from a single center were enrolled. Cardiac MRI and 3D echo images were obtained on the same day when routine echo was obtained. On the same day, along with annual routine blood test, cardiac biomarkers N‐terminal pro‐B‐type natriuretic peptide levels (NT‐proBNP) and troponin‐I levels were also measured. Results: Cardiac MRI was feasible in all 50 subjects. Three‐dimensional echo and 2D echo images were of poor quality in four subjects. With a median duration of remission of 10 years, there were four subjects with mild LV dysfunction (cardiac MRI LV EF of<53%). None had MRI EF <50%, and nine subjects had LVEF <55%. M‐mode echo overestimated EF more than 2D and 3D echo. Two‐dimensional and 3D echo methods had much tighter limits of agreement for LV EF. For measurement of LVEF, 3D echo had a lower % error than 2D echo or M‐mode echo. One subject had an abnormal troponin‐I level and another one had an elevated NT‐proBNP. Conclusions: Three‐dimensional echo can be performed in most adolescent cancer survivors, and it correlates well with MRI. Further large‐scale research is required in assessing utility of cardiac biomarkers in pediatric cancer survivors.